2020
DOI: 10.3390/ani10040580
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Fungal Phytases Can Affect Growth Performance, Nutrient Digestibility and Blood Profile of Broilers Fed Different Levels of Non-Phytic Phosphorous

Abstract: A total of 420 day old chicks were divided into seven groups (5 replicates of 12 chicks/group) fed isoproteic and isoenergetic diets. The control group was fed diets containing 0.50%, 0.45% and 0.40% of non-phytic phosphorous (nPP) in starter (1–35), grower (37–56) and finisher (57–64 d) periods, respectively. The three intermediate nPP (IntnPP) groups were fed diets with 0.40%, 0.35% and 0.30% nPP according to the growth period and were submitted to three dietary treatments: unsupplemented; supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…A similar trend was also observed during the entire experimental period (1-21 days), with birds fed the SBM diet and the 250 g/kg LP diet supplemented with PHY showing the highest BWG and FI compared with those in the other treatments. In line with the present finding, the positive influence of PHY supplementation on broiler performance has been well established (Wu et al 2004;Cowieson et al 2006;Selle et al 2012;Babatunde et al 2019;Ciurescu et al 2020;Attia et al 2020). However, Woyengo et al (2008) did not observe any improvement in performance as a result of supplementing broiler diet with PHY.…”
Section: Performance Of Broiler Chickenssupporting
confidence: 90%
“…A similar trend was also observed during the entire experimental period (1-21 days), with birds fed the SBM diet and the 250 g/kg LP diet supplemented with PHY showing the highest BWG and FI compared with those in the other treatments. In line with the present finding, the positive influence of PHY supplementation on broiler performance has been well established (Wu et al 2004;Cowieson et al 2006;Selle et al 2012;Babatunde et al 2019;Ciurescu et al 2020;Attia et al 2020). However, Woyengo et al (2008) did not observe any improvement in performance as a result of supplementing broiler diet with PHY.…”
Section: Performance Of Broiler Chickenssupporting
confidence: 90%
“…Nevertheless, Santos et al [29] indicated that the addition of phytase (500 FTU/kg) in broilers' diet can increase body weight gain in the starter stage, but does not affect the finisher stage. This may be due to gut maturation and less inorganic phosphorous requirements during the finisher period as well as stability of gut microbiota [2][3][4][5]. The result mentioned above confirmed that phytase is one of the necessary elements of FWB in the broilers' growth at the starter stage.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 54%
“…WB has fewer soluble pentose and hexose; however, after fermentation, pentose, and hexose respectively increased from 75. 3 With 1 ng LPS, the NO production increased to about 120 μmol on 10 7 chPBMCs.…”
Section: Wheat Bran (Wb) and Fermented Wheat Bran (Fwb) Characteristicsmentioning
confidence: 93%
See 2 more Smart Citations